The research of the drilling pipe's small-scale mode used in acoustic telemetry while drilling - Haiming Xie; Jing Zhou; Feng Zhang (Functional Materials, 2017)
The acoustic telemetry technology while drilling has a greater advantage in the transmission rate and the application of media than the commercial mud pulse mode and electromagnetic wave mode. There are limits to the existence of the periodic drill pipe acoustic transmission transmission model, which can only calculate the acoustic transmission characteristics of two kinds of periodic structures and the acoustic transmission characteristics of the composite structures with arbitrary cross section, but the variable cross-section or various special-shaped drill strings. According to the characteristics of the small scale structure of drill string, a small scale model of the drill string in the data transmission is set up by using the theory of longitudinal vibration of structures, in which the small scale vibration transfer function of cylindrical rods with different variable cross sections is analyzed. According to certain boundary conditions, the vibration transfer characteristics of drill string are obtained, and the simulation research is completed. Показано, что технология акустической телеметрии в процессе бурения композитных
структур имеет большое преимущество в скорости и способах передачи данных по
сравнению с режимом электромагнитной волны и обычным методом измерения колебаний
бура. Рассмотрены возможности метода акустической передачи данных бурильных труб,
которые позволяют рассчитать акустические характеристики периодических структур и
композитных структур при произвольном поперечном сечении и для различной специальной
формы сверла. В соответствии с характеристиками мелкоструктурной бурильной скважины
модель бурильных стержней рассматривается с помощью теории продольных колебаний
конструкций, в которой анализируются малые передаточные вибрации цилиндрических
стержней различных сечений.